The Analisis Efektivitas dan Efisiensi Pengelolaan Keuangan Guna Menilai Kinerja Keuangan Sekolah Dasar - Halimah Al Zaqi Sembiring; Riandani Rezki Prana (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
The purpose of this study was to analyze the financial performance of the Uli Arga Marindal Integrated Islamic Elementary School for the January-June and July-December 2022 periods using a qualitative approach. The data sources used are primary data, namely interviews, documentation and in-depth observation as well as secondary data with literature review related to the analysis of effectiveness and efficiency. The results of the research analysis show that financial performance in a state of Effective Financial Management is going well, positive contributions from schools and the community, financing is obtained from income (SPP and BOS/Others). Regular monitoring to encourage effectiveness and minimize financial fraud. Evaluation and accountability form the basis for future planning. The effectiveness ratio was 76.39% (less effective), increasing in the next period to 91.52% (effective). First financial ratio efficiency analysis: Liquidity, schools are declared liquid but fail to optimally utilize current assets or detect idle funds. Activity ratios: TAT and WCT show a lot of funds invested in fixed assets and crises; While FAT is in good condition. Efficiency analysis also uses efficiency ratio: revenue efficiency of 65.7% (quite efficient) and 47.77% (efficient) in the following period. The last operational efficiency ratio was 123.76% (inefficient) and increased to 52.42% (quite efficient) in the following period. This research still has many limitations, the object is only SD IT Uli Arga, limited effectiveness and efficiency of financial management in the two previous periods. So that the research results cannot be globalized, it is hoped that further researchers will extend the research period in order to get maximum results. SD Uli Arga should start developing cooperatives as an additional source of income, pay attention to the use of current assets and fixed asset investments, in order to increase effectiveness and plan for better efficiency